2010
DOI: 10.1258/acb.2010.009171
|View full text |Cite
|
Sign up to set email alerts
|

Serum testosterone levels measured by isotope dilution-liquid chromatography–tandem mass spectrometry in postmenopausal women versus those in women who underwent bilateral oophorectomy

Abstract: The ID-LC-MS/MS assay measures serum testosterone with acceptable accuracy and is useful in female samples, supporting the conclusion that the postmenopausal ovary contributes to circulating testosterone. To our knowledge, our analytical method compares favourably to similar published methods in terms of sensitivity. The sensitivity and specificity of this method comply with the reference method for measurement of testosterone in serum samples of women, children and men suffering from hypogonadism and can also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 15 publications
1
22
2
Order By: Relevance
“…Several studies also showed that women with bilateral oophorectomy had lower testosterone levels than those in natural postmenopausal women (92)(93)(94). Bui et al reported that a significant decrease was found in testosterone levels after bilateral oophorectomy, whereas no significant difference was found after natural menopause by using the developed isotope dilution-liquid chromatography-tandem mass spectrometry (95). However, more recently, it has been shown that levels of testosterone and DHEA-S did not differ significantly between surgically and naturally menopausal women with a mean age of 52.4 years (96).…”
Section: Site Of Androgen Production In Postmenopausal Womenmentioning
confidence: 99%
“…Several studies also showed that women with bilateral oophorectomy had lower testosterone levels than those in natural postmenopausal women (92)(93)(94). Bui et al reported that a significant decrease was found in testosterone levels after bilateral oophorectomy, whereas no significant difference was found after natural menopause by using the developed isotope dilution-liquid chromatography-tandem mass spectrometry (95). However, more recently, it has been shown that levels of testosterone and DHEA-S did not differ significantly between surgically and naturally menopausal women with a mean age of 52.4 years (96).…”
Section: Site Of Androgen Production In Postmenopausal Womenmentioning
confidence: 99%
“…In this case, the synthesis of D 5 -GP and D 4 -DMBA could be used to provide an easily prepared isotope-labeled steroid hormone. Based on the previously described investigation, in this study D 5 -GP and D 4 -DMBA reagents were synthesized. D 5 -GP reagent (9 g) was obtained with a yield of 89%.…”
Section: -37mentioning
confidence: 99%
“…3 The internal standards were tested for purity prior to the development of the method and both internal standards co-eluted with endogenous testosterone. Even though our observations differ from those reported by Owen and Keevil, we agree that the choice of internal standard is crucial.…”
mentioning
confidence: 99%